Relation of Soil Physical Parameters and Dominant Vegetation with Infiltration Capacity in Latuppa Sub-Watershed Palopo Indonesia - Witno Witno; Yumna Yumna; Abdul Rahim (Jurnal Biodjati, 2024)
The inflitration capacity is the soil’s ability to accommodate water that seeps into the soil, reducing surface runoff that will cause flooding, such as in the downstream area of Palopo city. This study aimed to determine the influence of dominant vegetation and soil physical characteristics on infiltration in the upstream area of the Latuppa Sub-Das, Mungkajang District, Palopo city. Data collection was carried out by direct observation in the 2yumnaunanda588@gmail.com field in a purposive manner in 10 plots, which represent the condition of vegetation in the upstream area of the Latuppa watershed, and each plot consisted of 3 replications to observe infiltration and soil samples. The data were analyzed via the rational method, the Horton method, and vegetation index analysis. Additionally, the data were analyzed via simple linear regression and multiple regression analysis to determine the influence of the dominant vegetation and physical characteristics of the soil on the infiltration capacity. The highest infiltration capacity was found in plot 10, with an infiltration capacity of 107.5 mm/minute (6,450 mm/hour) and an average infiltration rate of 0.4 mm/minute (24 mm/hour). The dominant vegetation cover is Cananga odorata, with a vegetation index value of 78.41%. Plot 10 has a height of 362.79 masl, a gentle slope, a crumbly soil structure, a clay sand texture, a very high soil density and 2.10% organic matter. Based on observations and data analysis, the factors that influence the infiltration capacity in the upstream area of the Latuppa subwatershed are vegetation conditions, altitude, slope and physical properties of the soil.